(untitled) (Lakar: Jurnal Arsitektur, 2026)
The rapid development of urban areas driven by educational activities, student housing, and commercial functions affects the visual quality and legibility of urban spaces. The Sigura-gura Street corridor in Malang City is one of the areas experiencing such dynamics. This study aims to identify and analyze the elements of city image based on Kevin Lynch’s theory, namely paths, edges, districts, nodes, and landmarks, in order to determine the level of area legibility. In terms of state of the art, previous studies in Indonesia have widely applied Lynch’s theory to commercial and residential areas; however, studies focusing on educational corridors with multifunctional characteristics and high mobility remain limited. This research employs a descriptive qualitative approach through field observations, documentation, brief interviews, and visual analysis of the area. The results indicate that the path element is the most dominant component due to the high intensity of vehicle and pedestrian movement. The edge element is represented by the river serving as a natural and administrative boundary between two sub-districts. The district is characterized by an educational environment and student housing supported by commercial activities. The node is identified at Muhajirin Mosque as a center of social and religious activities, while the main landmark is ITN Malang Campus, which functions as a strong visual orientation point. Overall, the corridor possesses a relatively strong city image structure but requires visual improvements to enhance its identity and environmental quality. This study is expected to provide recommendations for organizing educational corridors in Malang City.